2013
DOI: 10.1155/2013/629468
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Theorems for Fixed Points of Multivalued Strictly Pseudocontractive Mappings in Hilbert Spaces

Abstract: LetKbe a nonempty, closed, and convex subset of a real Hilbert spaceH. Suppose thatT:K→2Kis a multivalued strictly pseudocontractive mapping such thatF(T)≠∅. A Krasnoselskii-type iteration sequence{xn}is constructed and shown to be an approximate fixed point sequence ofT; that is,limn→∞d(xn,Txn)=0holds. Convergence theorems are also proved under appropriate additional conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Thus, our result is applicable to all classes of demicontractive mappings. Furthermore, our theorems extend and improve the results of Chidume and Ezeora [18], Chidume et al [17], and Isiogugu and Osilike [19] and complement the results of Dhompongsa and Panyanak [16], Dhompongsa et al [9], Leustean [11], Shahzad and Markin [13], and Sokhuma [20] and results of a host of other authors on iterative approximation of fixed points in CAT(0) spaces.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, our result is applicable to all classes of demicontractive mappings. Furthermore, our theorems extend and improve the results of Chidume and Ezeora [18], Chidume et al [17], and Isiogugu and Osilike [19] and complement the results of Dhompongsa and Panyanak [16], Dhompongsa et al [9], Leustean [11], Shahzad and Markin [13], and Sokhuma [20] and results of a host of other authors on iterative approximation of fixed points in CAT(0) spaces.…”
Section: Introductionsupporting
confidence: 84%
“…Very recently, Chidume and Ezeora extended the result of Chidume et al [17] to a finite family of multivaluedstrictly pseudocontractive mappings in real Hilbert spaces. The following theorem is their main result.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several authors have studied iterative algorithms for approximating fixed points of various classes of nonlinear mappings (including hemicontractive mapping); see, for example, [5,8,14,15,21] and the references cited therein. In 2007, Rafiq [13] introduced the following Mann-type implicit iteration process and showed that the process converges strongly to a fixed point of a continuous hemicontractive mapping T from a compact and convex subset C of a real Hilbert space into itself:…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the existence of fixed points and their approximations for multi-valued contraction and nonexpansive mappings and their generalizations have been studied by several authors (see, e.g., [1,3,4,6,9,[11][12][13]15] and the references therein).…”
Section: Introductionmentioning
confidence: 99%